2005
DOI: 10.1212/01.wnl.0000148599.18397.d2
|View full text |Cite
|
Sign up to set email alerts
|

Differential vestibular dysfunction in sudden unilateral hearing loss

Abstract: Auditory and vestibular function was examined in 29 patients with unilateral sensorineural hearing loss to identify characteristic vestibulocochlear lesion patterns. In 45%, a vestibular lesion was found, of which 53% had a combined impairment of the cochlea and the ipsilateral posterior semicircular canal, possibly reflecting vascular disease in the common cochlear artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
42
0
6

Year Published

2006
2006
2106
2106

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 8 publications
5
42
0
6
Order By: Relevance
“…In a study on acute sensorineural hearing loss, 14% had a complete vestibular loss defined as involvement of all three SCCs, 31% a partial vestibular loss defined as involvement of one or two SCCs and 55% no measurable SCC loss. In the group with a partial lesion, all patients had the PC affected [75]. In another study on acute unilateral hearing loss with vestibular symptoms, there is an impairment of the PC in 74%, of the HC in 41% and of the AC in 30% [76].…”
Section: Sudden Sensorineural Hearing Loss (Ssnhl)mentioning
confidence: 94%
“…In a study on acute sensorineural hearing loss, 14% had a complete vestibular loss defined as involvement of all three SCCs, 31% a partial vestibular loss defined as involvement of one or two SCCs and 55% no measurable SCC loss. In the group with a partial lesion, all patients had the PC affected [75]. In another study on acute unilateral hearing loss with vestibular symptoms, there is an impairment of the PC in 74%, of the HC in 41% and of the AC in 30% [76].…”
Section: Sudden Sensorineural Hearing Loss (Ssnhl)mentioning
confidence: 94%
“…The horizontal VOR was elicited by passive head thrusts [7] and did not differ from that of healthy controls. Blinks were not used by either patient to trigger saccades ( Fig.…”
mentioning
confidence: 74%
“…Twelve patients out of 71 patients had unilateral hearing loss. In a study to find the vestibular lesions in patients with unilateral hearing loss, researchers found that in the group of 29 patients, 45% showed presence of vestibular dysfunction 13 .…”
Section: Discussionmentioning
confidence: 99%